Plantas daninhas sob a copa de árvores em função da consorciação e densidades de plantio - Souza, Aline Danielle de (Universidade Federal Rural do Semi-Árido, 2011)
Two experiments on planting density (E1) and intercropping (E2) were conducted in Mossoro, Rio Grande do Norte, aiming to: a) evaluate the growth of tree species; b) evaluate the floristic composition and the growth of weeds under tree canopies; c) estimate the soil nutrient content under tree canopies in E2. The experimental design of randomized blocks with three or four replications, respectively, was used in both experiments. In E1, Gliricídia sepium (G) and Mimosa caesalpiniifolia benth (S) were submitted to the following planting densities: 400, 600, 800, 1000, and 1200 plant/ha-1. In E2, G, neem (Azadirachta indica) (N), and S were grown in monoculture and intercropped in three-line plots with four plants (GGG, NNN, SSS, SGS, NGN, GNG, SNS, SGS, and NSN, where each letter is one line). The evaluations, in both experiments, were done 1 and 2 years after planting the trees. In E1, the higher the planting density the lower the weed dry matter (MS) and fresh matter (MF), the amount of weeds (NPD) under the canopies, the S and G canopy diameter (DC), and G plant height (AP). It was observed that there is a relationship between AP and NPD under the canopy of G. The higher the NPD the higher the AP. In E2, it was observed a relationship between S plants, AP and DC. The S with higher AP and DC presented lower weed MS and MF under its canopy. The level of phosphorus in soil under the canopy was lower in the intercrop GNG in E2. N plants with higher AP and DC presented lower level of potassium under its canopy. Besides, N plants with higher AP have lower base saturation in soil
Weeds under tree canopies due to intercropping and planting densities
Keywords: Intercropping; plant spacing; tree species; Consórcio; espaçamento; espécies arbóreas; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA